PROGRESIVITAS PEMIKIRAN HUKUM UMAR IBN KHATTAB - Fahmi Assulthoni (LP2M IAI Miftahul Ulum Pamekasan, 2015)
This article deals with the understanding of Moslem fundamentally critisizing an interpretation assumed as contradictive with a certain group or community. Thus, it is continuously said that it is out of Islamic philosophical rule, and so on. Basically, these viewpoints were proposed by a great Islamic clergy, besides he was a companion of Prophet Muhammad saw, Umar who had a capability to interprete “nash” and was also contradictive with most of the companions, eventhough with the text itself.